Novel liquid chromatographic method for simultaneous estimation of pioglitazone and glimepiride in rat plasma by solid phase extraction: application to preclinical pharmacokinetic studies - Musmade, Prashant B; Talole, Kranti B; Deshpande, Praful B; Karthik, Arumugam; Pathak, Shriram M; Pandey, Sureshwar; Udupa, Nayanabhirama (Arzneimittelforschung, 2011)
The need for a reliable bioanalytical method is of primary importance during preclinical studies. The aim of the present study was simultaneous determination of pioglitazone (CAS 111025-46-8) (PIO) and glimepiride (CAS 93479-97-1) (GLM) in plasma of rats. A high-performance liquid chromatographic method has been developed and validated using C18 column and UV detector. A mobile phase composed of acetonitrile and ammonium acetate buffer pH 4.5 in the ratio of 55 : 45%. The plasma samples clean-up was carried out using solid phase cartridges. The method was in the linear range of 50–8000 ng/mL for PIO and 50-2000 ng/mL for GLM. The coefficient of regression was found to be ≥ 0.99. Precision and accuracy were within the acceptable limits, as indicated by relative standard deviation varying from 1.5 to 6.1% for PIO and 3.1 to 7.0% for GLM whereas the accuracy ranged from 97.0 to 106.4% for PIO and 96.5 to 106.4% for GLM. The mean extraction recovery was found to be 90.2 ± 4.5, 76.8 ± 2.8 and 85.2 ± 5.2% for PIO, GLM and internal standard, respectively. Moreover, PIO and GLM were stable in plasma, up to 30 days of storage at −70 °C and after being subjected to bench top, auto-sampler, and three freeze-thaw cycles. The developed method was applied for preclinical pharmacokinetic studies.
Keywords: Antidiabetic drugs; Glimepiride; Pharmacokinetics; Pioglitazone; Rat plasma; Solid phase extraction